Effects of anthelmintic treatment on ewe feed intake, digestion, milk production and lamb growth. (22nd September 2016) - ZHONG, R. Z.; CHENG, L.; WANG, Y. Q.; SUN, X. Z.; LUO, D. W.; FANG, Y.; BUSH, R. D.; ZHOU, D. W.
SUMMARY: Twenty Small Tailed Han (STH) and 20 Ujumqin (UJU) ewes naturally infected with gastrointestinal nematodes were randomly assigned to one of four treatments arranged in a 2 × 2 factorial design, receiving anthelmintic treatment (AT) or non-anthelmintic treatment (NonAT) prior to lambing. After lambing, the effects of AT on feed intake, digestion and milk yield in ewes, and the growth rates of lambs fed their mother's milk were assessed for 28 days. Faecal samples were collected to determine faecal egg counts (FECs), milk was collected to measure milk yield and ewes and lambs were weighed to quantify daily body weight change. The results showed that AT significantly increased ewe dry matter intake (2411 g/d for AT and 2209 g/d for NonAT) and decreased FECs (50 eggs/g for AT and 2655 eggs/g for NonAT). All ewes lost weight after lambing, but body weight loss in the AT (43 g/d) was significantly less than in NonAT (84 g/d), and STH ewes (70 g/d) lost more weight than UJU ewes (58 g/d). Anthelmintic-treated ewes produced more milk for their lambs to consume. However, the extent of these positive effects of AT differed between STH and UJU ewes. The average daily body weight gain of lambs in AT was higher than those in NonAT. In conclusion, effective AT in ewes before lambing benefits subsequent lactation in ewes and growth rate in lambs.